The mediating effect of innovation on the relationship between entrepreneurial competencies and business success in Malaysia - Azmi Umar (Tanjong Malim, 2019)
The mediating effect of innovation on the relationship between entrepreneurial competencies and business success in Malaysia by Azmi Umar